1

Is the proof below correct for the following premise?: ⊤ ⊢ (B → ¬B) → ¬B

1 B → ~B :AS

2 B :AS

3 ~B : → E1,2

4 ⊥

5 ~B :~I1-4

6 --

7 (B->~B)-> ~B :->I1-4

  • Here is a natural deduction proof checker: proofs.openlogicproject.org – lemontree Oct 25 '20 at 20:51
  • You should cite the rule name and source lines for ⊥, and the source lines for your last -> should be 1-5; otherwise your proof looks fine -- well done! – lemontree Oct 25 '20 at 20:54
  • @lemontree thank you!! – Pri Oct 25 '20 at 20:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.